Book clubs: an ethnographic study of an innovative reading practice in Spain. Issue 2 (3rd May 2016) - Álvarez-Álvarez, Carmen
ABSTRACT: The most innovative reading practices currently rely on the paradigm of dialogic reading. Book clubs, literary gatherings and study circles are emerging in different social spaces to promote reading and literary discussion amongst adults, and libraries, bookshops, cultural centres, etc. are increasingly developing strategies in this direction. Despite the vast development of reading clubs throughout Spain, empirical research on this phenomenon is still at the embryonic stage. This paper queries the ability of this practice to encourage the pleasure of reading, as well as civic and literary education. The results, obtained from an ethnographic study of nine book club meetings and six key informant interviews, show that the discussions contribute to: (1) developing a taste for reading, literature and reading habits; (2) fostering debate about values and learning about personal experiences related to the stories covered in the various readings; and (3) learning academic skills that go beyond the scope of an informal literary analysis. The main conclusion of our study is that book club meetings generate a very favourable context for literary analysis, as they foster reading innovation and the cultivation of literature, as well as promoting values education and adult learning from a dialogic perspective.